Effect of cobalt nanoparticles and cobalt ions on alkaloids production and expression of CrMPK3 gene in Catharanthus roseus suspension cultures - Fouad, Ahmed Sayed; Hafez, Rehab Mahmoud (Cellular and Molecular Biology, 2018)
The capabilities of cobalt ions (Co2+) and cobalt nanoparticles (CoNPs) in enhancing alkaloids accumulation in Catharanthus roseus suspension cultures were evaluated in relation to the expression of CrMPK3 gene. Four concentrations (5, 10, 15 and 20 mg/L) of each cobalt form were utilized in addition to control. Both forms induced oxidative stress that was more pronounced for Co2+ treatments. A positive correlation was observed between cobalt concentration and expression of CrMPK3 gene. However, a characteristic temporal expression profile was recorded for each cobalt form. Also, positive correlations were detected between both cobalt concentration and expression of CrMPK3 gene on one hand and the activities of antioxidant enzymes (SOD and APX) and alkaloids content on the other hand. Such correlations suggest CrMPK3 gene as a common player in cobalt-induced stress signaling; regardless of cobalt form. Results revealed the higher capability of Co2+, compared with CoNPs, in enhancing alkaloids accumulation. However, results supported CoNPs as a novel tool in manipulating cobalt-induced alkaloids production in C. roseus.